Slovarsko gradivo Ftičarjevega romana Za nápršnjek vedríne - Ulčnik, Natalija (Slavia Centralis, 2020)
Lexicographical Material in Ftičar’s novel Za nápršnjek vedríne Za nápršnjek vedríne (2004, 2006) by Jože Ftičar represents the first Slovene novel written in dialect. In a broader sense it can be considered the continuation and upgrading of the old Prekmurje literary production. The present paper aims to analyze and evaluate the lexicographical material issued as a supplement to the novel. In it the author gathered almost 3,000 entries for items that he assumed the reader of standard Slovene would have difficulty understanding. The dictionary has also proven significant for Prekmurje dialect lexicography, since it includes entries that had not yet been registered.